Inequities in consistent condom use among sexually experienced undergraduates in mainland China: implications for planning interventions - Fang Ruan; Guochen Fu; Yongfu Yan; Yajie Li; Yulin Shi; Lan Luo; Xin Li; Bolun Zhang; Qinxin Gong; Zihan Fu; Yuhang Gan; Mengge Pan; et al. (BMC, 2019)
Abstract Background Since pre-exposure prophylaxis (PrEP) is mainly prescribed to high-risk uninfected individuals, consistent condom use (CCU) continues to be recommended as an inexpensive, feasible, practical and acceptable way to prevent the general population from acquiring and transmitting HIV through sexual intercourse. The objective of this cross-sectional study was to compare the relative importance of various determinants of CCU among sexually experienced undergraduates in mainland China so as to assess and subsequently to suggest ways to eliminate inequities in its use. Method From September 10, 2018, to January 9, 2019, an anonymous self-administered online questionnaire was voluntarily completed by 12,750 participants distributed across 30 provinces in mainland China (except for Tibet). The present analysis was restricted to 2054 sexually experienced undergraduates. Pearson's chi-square test and Logistic regression models were chosen to analyze the factors associated with CCU. Results The overall rate of CCU was 61.3% [95% confidence interval (CI) = 59.2-63.4%]. CCU was inequitably distributed since enabling factors exerted greater effects than predisposing and need variables. Compared with heterosexual men, heterosexual women [adjusted odds ratio (AOR) = 0.78, 95% confidence interval (CI):0.64-0.96)], non-heterosexuals men (AOR = 0.64, 95% CI:0.45-0.92) and women (AOR = 0.68, 95% CI:0.47-0.99) were less prone to using condoms consistently. Those with more resources [i.e., higher levels of self- efficacy for condom use (AOR = 2.86, 95% CI:2.35-3.49) and being knowledgeable of the national AIDS policy (AOR = 1.50, 95% CI:1.23-1.82)], and those with lower need for condoms [i.e., late initiation of sexual activity (AOR = 1.34, 95% CI:1.09-1.64) and single sexual partner (AOR = 1.68,95% CI:1.21-2.33)] were more likely to be consistent condom users. Conclusions In order to increase consistency of condom use and simultaneously reduce the remaining inequities, a comprehensive intervention measure should be taken to target heterosexual women, non-heterosexual men and women, and those with higher need for condoms, improve their condom use self- efficacy and raise their awareness of the national AIDS policy.